Russell Wheeler Davenport papers - Davenport, Russell W. (Russell Wheeler), 1899-1954.; Davenport, Russell W. (Russell Wheeler), 1899-1954.
Correspondence, memoranda, diaries, writings, speeches, research material, political files, biographical material, legal and financial papers, photographs, and other papers relating primarily to Davenport's career as a writer and editor with Fortune and Life magazines, his involvement with the Republican Party, his work with the Institute for Creative Research, New York, N.Y., his writings including The Dignity of Man (1955), his service in World War I and II, and his personal life. Includes material pertaining to Davenport's work with Republican Advance and his management of Wendell W. Willkie's bid for the Republican presidential nomination in 1940. Topics include Davenport's research in public policy matters, his work against communism and fascism and for democracy, peace, and world government, and his interest in astrology and psychoanalysis.
Correspondents include Robert Chapman Bates, Raymond Leslie Buell, Harriet Cowles, Cornelia Whipple Davenport, Marcia Davenport, Natalie Potter Davenport, Dwight D. Eisenhower, Eric Hodgins, Paul G. Hoffman, Herbert Hoover, Harry Lloyd Hopkins, Robert L. Johnson, Joseph P. Kennedy, Walter Lippmann, Parker Lloyd-Smith, Henry Cabot Lodge, Clare Boothe Luce, Henry Robinson Luce, Archibald MacLeish, Henry V. Poor, Phelps Putnam, John D. Rockefeller, Nelson A. Rockefeller, Elmo Roper, William Siegmund Schlamm, Joseph M. Scribner, Simon and Schuster, inc., Blackwell Smith, the Thacher School, and Adelaide Walker.
Author, editor, and political activist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bates, Robert Chapman, -- 1901-1942 -- Correspondence; Buell, Raymond Leslie, -- 1896-1946 -- Correspondence; Cowles, Harriet -- Correspondence; Davenport, Cornelia Whipple, -- 1865-1946 -- Correspondence; Davenport, Marcia, -- 1903-1996 -- Correspondence; Davenport, Natalie Potter -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Hodgins, Eric, -- 1899-1971 -- Correspondence; Hoffman, Paul G. -- 1891-1974 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hopkins, Harry L. -- 1890-1946 -- Correspondence; Johnson, Robert L. -- 1894-1966 -- Correspondence; Kennedy, Joseph P. -- 1888-1969 -- Correspondence; Lippmann, Walter, -- 1889-1974 -- Correspondence; Lloyd-Smith, Parker -- Correspondence; Lodge, Henry Cabot, -- 1902-1985 -- Correspondence; Luce, Clare Boothe, -- 1903-1987 -- Correspondence; Luce, Henry Robinson, -- 1898-1967 -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Poor, Henry V. -- Correspondence; Putnam, Phelps, -- 1894-1948 -- Correspondence; Rockefeller, John D., -- Jr. -- 1874-1960 -- Correspondence; Rockefeller, Nelson A. -- 1908-1979 -- Correspondence; Roper, Elmo, -- 1900-1971 -- Correspondence; Schlamm, William S. -- 1904-1978 -- Correspondence; Scribner, Joseph M., -- 1897-1979 -- Correspondence; Smith, Blackwell, -- 1904- -- Correspondence; Walker, Adelaide -- Correspondence; Willkie, Wendell L. -- 1892-1944.; Institute for Creative Research (New York, N.Y.); Republican Advance (Organization); Republican Party (U.S. : 1854- ); Simon and Schuster, inc. -- Correspondence; Thacher School (Ojai, Calif.) -- Correspondence; Fortune; Life; American periodicals; Anti-communist movements; Anti-fascist movements; Astrology; Democracy; International organization; Peace; Psychoanalysis; Political planning; World War, 1914-1918.; World War, 1939-1945.; Authors; Editors; Political activists